A efetivação prioritária dos direitos fundamentais e da doutrina da proteção integral da população infantojuvenil (crianças e adolescentes) como instrumentos de transformação social - Prado, Paulo Roberto Jorge do (2023)
The Child and Adolescent Statute-ECA, Law No. 8069 of July 13, 1990 appears in the national legal system as a direct form of regulation of the provisions of Art. 227 of the Federal Constitution, which absorbed the dictates of the Doctrine of Integral Protection and contemplates the Principle of Absolute Priority. The ECA also comes to regulate the aforementioned constitutional provision, which, in turn, observed the rule set out in the Doctrine of Integral Protection, decisively contemplating the Principle of Absolute Priority, in the eagerness to standardize the situations and legal relationships related to children and adolescents, provoking a great national debate. Calling the powers that be, Academy, Civil Society, the reflection of abandonment of Actions, Projects, Policies and guidelines guided by the reality experienced in the Country, involving Children and Adolescents, where we routinely experience alarming rates of separation and social abandonment. It can be seen in this paradigm that the Doctrine of full protection is inspired by international regulations, materialized in treaties and conventions. By asking how to use all this legislation, these instruments to strengthen children's citizenship and, consequently, achieve the real realization of the Fundamental Rights and the Doctrine of Integral Protection posited in the Statute of the Child and Adolescent as an instrument of social transformation, we put ourselves in the exercise to carry out a qualitative bibliographical and documentary study with the objective of deepening studies on the fundamental rights of children and adolescents from the perspective of the Doctrine of Integral Protection and based on the provisions of the Constitution of the Federative Republic of Brazil and the Statute of the Child and of the Adolescent, in order to reach the real meaning of these fundamental guarantees and the necessary measures for implementation and social transformation.